Digitalisasi Sebagai Upaya Peningkatan Kepatuhan Penggunaan Obat Pasien Tuberkulosis: Studi Literatur - Kartikawati, Nurfina Dian; Febriani, Anisa Putri; Rizki, Rahmania Hafidhotur; Sari, Lutfiana (Universitas Muhammadiyah Magelang, 2024)
Patient adherence to TB treatment regimen is essential to ensure recovery and prevent drug resistance. The use of drug reminder applications in the management of Tuberculosis (TB) is increasingly growing in the digital era. This literature aims to review the effect of drug reminder applications on TB patient adherence. The method used is a systematic literature review by searching various relevant scientific databases, such as Crossref and Google Scholar, for articles published in the last two years. The keywords in this study are: Tuberculosis; Drug Adherence; Drug Reminder Application. The literature search was conducted by combining Boolean search terms (